SCIENTIFIC AND TECHNICAL INFORMATION SERVICES FOR INNOVATIVE INDUSTRIES & BUSINESS INFORMATION PRODUCTS WITH SPECIAL REFERENCES TO INDONESIA - Utari Budihardjo, Heddy Suprihadi (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 1996)
To suport and motivated industrial growth as well as to keep up industries with global changed in economy, trade and technology, there should be an applicable system of collection of information and monitoring of changes that will easely be retrieved by industrial users. The availability of information network on industry, such as industrial Information System Network (SINAS), many important database centres, as well as standard and patent information also play important role in providing appropriate information to develop better industrial products in Indonesia.